2014
DOI: 10.1111/cla.12092
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caribbean Islands in the diversification and biogeography of Neotropical Heraclides swallowtails

Abstract: Numerous hypotheses on the evolution of Neotropical biodiversity have stimulated research to provide a better understanding of diversity dynamics and distribution patterns of the region. However, few studies integrate molecular and morphological data with complete sampling of a Neotropical group, and so there has been little synthesis of the multiple processes governing biodiversity through space and time. Here, a total-evidence phylogenetic approach is used to reconstruct the evolutionary history of the butte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 118 publications
(229 reference statements)
8
24
1
Order By: Relevance
“…The sole species of the temperate subgenus Alexanoria is sister to the clade composed of Agehana + Chilasa + Pterourus . Both subgenus and species group‐level relationships are consistent with results of previous studies (Condamine et al, ; Lewis et al, ; Shiraiwa et al, ; Zakharov et al, ). Within the New World Papilio , temperate and tropical taxa do not constitute monophyletic assemblages (Figure ; see also Supporting Information Appendix S2 Figure S2.2).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The sole species of the temperate subgenus Alexanoria is sister to the clade composed of Agehana + Chilasa + Pterourus . Both subgenus and species group‐level relationships are consistent with results of previous studies (Condamine et al, ; Lewis et al, ; Shiraiwa et al, ; Zakharov et al, ). Within the New World Papilio , temperate and tropical taxa do not constitute monophyletic assemblages (Figure ; see also Supporting Information Appendix S2 Figure S2.2).…”
Section: Resultssupporting
confidence: 90%
“…Our biogeographical reconstructions indicate that the most recent common ancestor of New World swallowtails is likely to have occupied both northern temperate and tropical latitudes and climatic tropics and temperate zones. Corroborating previous work (Lewis et al, ), we found that after a putative vicariance event c . 20 Ma, Heraclides diversified in the climatic and latitudinal tropics, with some lineages then dispersing to temperate latitudes and cooler climates in the late Miocene.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As suggested by present‐day behaviour of some species (Urquhart & Urquhart, ; Oliveira et al ., ; Srygley & de Oliveira, ), some ancestral populations were probably strongly vagile and colonized the continent across the open ocean. Reverse colonization from the Greater Antilles to the continent has been inferred for other groups, including Urocoptidae land snails (Uit de Weerd et al ., ), Heraclides swallowtail butterflies (Lewis et al ., ), Exophthalmus weevils (Zhang et al ., ), Anolis lizards (Nicholson et al ., ), Eleutherodactylus frogs (Heinicke et al ., ) and Amazona parrots (Russello & Amato, ).…”
Section: Discussionmentioning
confidence: 99%